2016
DOI: 10.1097/md.0000000000004163
|View full text |Cite
|
Sign up to set email alerts
|

Improving of bowel cleansing effect for polyethylene glycol with ascorbic acid using simethicone

Abstract: Background and Aim:Low-volume polyethylene glycol with ascorbic acid (PEG-Asc) use is reported to be as safe and effective as traditional 4-L polyethylene glycol use. However, PEG-Asc produces bubbles, which cause problems during colonoscopy. Data on the effects of using antifoaming agents such as simethicone with PEG-Asc are lacking. The aim of this CONSORT-prospective, randomized, observer-blinded, controlled trial is to compare the quality of bowel preparation and compliance between PEG-Asc users and PEG-As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(88 citation statements)
references
References 22 publications
4
84
0
Order By: Relevance
“…After listing the ADR in individual RCTs, the researchers decided to perform a post hoc subgroup analysis of the effect of SIM on ADR stratified according to the baseline ADR (the ADR in the non‐SIM group), due to the large gap between the highest ADR (46.4%; Yoo et al …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After listing the ADR in individual RCTs, the researchers decided to perform a post hoc subgroup analysis of the effect of SIM on ADR stratified according to the baseline ADR (the ADR in the non‐SIM group), due to the large gap between the highest ADR (46.4%; Yoo et al …”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the level of bowel cleansing, simethicone (SIM), a kind of oral antifoaming agent, has been added to several PEG‐based bowel preparation regimens, for it reduces bubbles in bowel segments so as to improve visualization of the colonic mucosa and promote emission of excessive gas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, modifications of the bowel preparation prescribed such as the addition of coffee [13] or the addition of simethicone as an anti-foaming agent [14]. A number of studies have demonstrated that the addition of simethicone to the bowel preparation improved the visibility [12,15] and a systematic review concluded that supplemental use of oral simethicone before endoscopy improves the small bowel visibility, decreases air bubbles in the colonic lumen but does not affect the completion rate of colonoscopies [16]. There is also improved visibility with pre-medication using simethicone before esophagogastroduodenoscopy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well established that the quality of the bowel preparation with regard to polyp and adenoma detection rates is critical [9]. Numerous measures such as single vs. split prep bowel preparation have been tested and split prep has been shown to result in better adenoma detection rates [10][11][12]. Similarly, modifications of the bowel preparation prescribed such as the addition of coffee [13] or the addition of simethicone as an anti-foaming agent [14].…”
Section: Discussionmentioning
confidence: 99%